Refleksi Realitas Sosial dalam Novel Qalbu Lail Karya Naguib Mahfouz: Kajian Sosiologi Sastra Swingewood - Albanjari, Nida Firdaus (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2025)
This study aims to analyze the reflection of social reality in Naguib Mahfouz's novel Qalbu Lail using Alan Swingewood's sociology of literature framework. This study aims to determine how the novel reflects social reality in Egypt, and to identify the messages and meanings contained therein. The research method used is descriptive qualitative with primary data in the form of the original text of the novel. Data analysis was carried out by identifying and classifying the themes of social reflection in the novel, then interpreted based on the concept of social realism and Swingewood's theory. The results of the study show that Qalbu Lail reflects various social issues, including a crisis of trust due to systemic injustice in terms of inheritance, intergenerational conflict between traditional values and modernity, and the influence of family structure on individual experiences. This novel also raises the theme of the search for justice, rejection of repressive social norms, and the importance of family and community support. In conclusion, Qalbu Lail is not only a literary work, but also a deep reflection of social reality in Egypt. This analysis emphasizes the role of literature as a medium for understanding and interpreting social structures, cultural values, and conflicts that occur in society. This study suggests that readers should understand the social and historical context when analyzing literary works, so that the meaning contained can be better understood.